Austenitic stainless steel

By optimizing the composition and processing techniques for austenitic stainless steel, the material achieves enhanced hardness, strength, ductility, and surface quality, addressing the limitations of existing austenitic stainless steels.

JP2025513824APending Publication Date: 2025-04-30POHANG IRON & STEEL CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024559964
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-03-10
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Existing austenitic stainless steels face limitations in yield strength, ductility, and surface properties, particularly when subjected to tempering rolling processes, which increase costs and reduce material stretchability.

Method used

The development of an austenitic stainless steel with a specific composition (C: 0.04-0.07%, Si: 0.3-0.6%, Mn: 0.5-1.5%, Cu: 0.1-0.4%, Mo: 0.05-0.2%, Ni: 8.0-9.0%, Cr: 18.0-19.0%, N: 0.02-0.05%) and processing techniques that include hot rolling, cold rolling, and controlled annealing to achieve ultra-fine grain structures, enhancing hardness, strength, ductility, and surface quality.

Benefits of technology

The resulting austenitic stainless steel exhibits improved hardness, high strength-high ductility, excellent drawability, and sound surface properties, including resistance to surface cracking and enhanced pitting potential, thereby overcoming the limitations of existing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025513824000001_ABST
    Figure 2025513824000001_ABST
Patent Text Reader

Abstract

The object of the present invention is to provide an austenitic stainless steel having no surface cracks in the banded area and excellent surface roughness by proposing an ultrafine grain manufacturing technology that realizes hardness, high strength-high ductility, drawability, banding resistance, and sound surface properties of the banded area. [Solution] The austenitic stainless steel of the present invention contains, by weight, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, 0.02-0.05% N, with the remainder being Fe and unavoidable impurities, has a thickness of 0.4-2.0 mm, an average crystal grain size (d) value at the center of the thickness is 3 to 10 μm, a martensite fraction after cold rolling is 60% or more, and a misorientation angle of 0.02 to 0.05 mm after cold rolling annealing is 0.02 to 0.05 mm. The fraction of angles 15° or greater is 95% or greater, the pitting potential value is 250mV or greater, the surface roughness (Ra) during tension is 0.50μm or less at 30%, the surface roughness (Ra) during tension is 0.36μm or less at 20%, and the surface roughness (Ra) during tension is 0.25μm or less at 10%, the limiting drawing ratio for age cracking during drawing is 2.0 or greater, the average earring height is 2.2mm or less, and no bending cracks occur after a 180° bending experiment.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an austenitic stainless steel, and more particularly to an austenitic stainless steel having improved hardness, high strength-high ductility, drawability, banding resistance and surface properties. [Background technology]

[0002] In general, austenitic stainless steels are used in a variety of applications, such as transportation parts and building parts, due to their excellent formability, work hardening ability, and weldability. However, 304 series stainless steel and 301 series stainless steel have a yield strength of only 200 to 350 MPa, which limits their application to structures. Therefore, in order to obtain a higher yield strength in general-purpose 300 series stainless steel, a temper rolling process is generally used. However, the temper rolling process has problems such as increased costs and very poor elongation of the material.

[0003] Patent Document 1 describes a manufacturing method for 300 series stainless steel for use as a laser metal mask for photoetching, in which cold-rolled annealed material is temper-rolled, and then subjected to two SR (Stress Relief) heat treatments to reduce bending even after half-etching. However, Patent Document 1 only describes a manufacturing technique for controlling the etchability and bending after etching, and does not include technical content for structural parts with a thickness of 0.4 to 2.0 mm. * ([C]+[N]-9.2 * [Si]-8.1 * [Mn]-13.7 * [Cr]-20 * [Ni]+[Cu]-18.7 * Since the ASP (Austenitic Stability Parameter) value calculated by [Mo] is in the range of 30 to 50, there is a problem that deformation-induced martensitic transformation occurs suddenly during forming such as tensile testing, resulting in a decrease in elongation ratio.

[0004] Patent Document 2 proposes a method of performing heat treatment for a long period of time of 48 hours or more at a temperature of 600 to 700°C to manufacture an average crystal grain size of 10 μm or less. However, the method proposed in Patent Document 2 has problems in that productivity is reduced and manufacturing costs are increased when it is implemented on an actual production line. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2016 / 043125 [Patent Document 2] JP 2020-050940 A Summary of the Invention [Problem to be solved by the invention]

[0006] The object of the present invention is to provide an austenitic stainless steel having no surface cracks in the banded area and excellent surface roughness by proposing an ultrafine grain manufacturing technology that realizes hardness, high strength-high ductility, drawability, banding resistance, and sound surface properties of the banded area. [Means for solving the problem]

[0007] The austenitic stainless steel of the present invention contains, by weight percent, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, 0.02-0.05% N, with the remainder being Fe and unavoidable impurities; The Σ value represented by the following formula (1) may be 180 or more and 240 or less. Formula (1):Σ=105+146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu]

[0008] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight percentage of each element, d represents the average crystal grain size (μm), and SPM_El represents the difference in elongation rate (%) before and after Skin Pass Milling. Furthermore, the austenitic stainless steel according to the present invention may have an Ω value represented by the following formula (2) of 2500 or more. Equation (2): Ω = YS * El-500 * ([Ni]+[Cr]+[Cu]+[Mn]) In the formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight percentage of each element, YS represents the yield strength (MPa), and El represents the elongation rate (%).

[0009] The austenitic stainless steel according to the present invention may have an Austenitic Stability Parameter (ASP) value, represented by the following formula (3), of -5 to 12. Formula (3): ASP value = 551-462 * ([C]+[N])-9.2 * [Si]-8.1 * [Mn]-13.7 * [Cr]-29 * ([Ni]+[Cu])-18.5 * [Mo] In the formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight percentage of each element.

[0010] Furthermore, the austenitic stainless steel according to the present invention may have a Π value represented by the following formula (4) of 6000 or more. Equation (4): Π = 100 * FCRR(Final Cold Rolling Ratio,%)+100 * ASP(Austenitic Stability Parameter)+CAT(Cold Annealing Temperature,℃) In the above formula (4), FCRR means the reduction rate during cold rolling before final cold roll annealing, ASP means the value of formula (3), and CAT means a value defined by the temperature of the final cold rolled and annealed steel material.

[0011] Furthermore, in the austenitic stainless steel according to the present invention, when the total thickness is taken as t, the average crystal grain size (d) value at the center of the thickness in the TD (Transverse Direction) plane may be 3 to 10 μm. Moreover, the t may be 0.4 to 2.0 mm.

[0012] In addition, the austenitic stainless steel according to the present invention may have a martensite fraction (%) of 60% or more in a cold-rolled material when analyzed at the center of thickness in a transverse direction (TD) plane using an electron backscatter diffraction (EBSD) analyzer. In addition, when the center of the thickness of the transverse direction (TD) plane is analyzed by an electron backscatter diffraction (EBSD) pattern analyzer, the percentage (%) of misorientation angles of 15° or more after cold rolling and annealing may be 95% or more.

[0013] The austenitic stainless steel according to the present invention may have a pitting potential value in a 3.5% NaCl solution at 30° C. of 250 mV or more. In addition, the surface roughness (Ra) when tensile is 0.50 μm or less at 30%, the surface roughness (Ra) when tensile is 0.36 μm or less at 20%, and the surface roughness (Ra) when tensile is 0.25 μm or less at 10%. In addition, the limiting drawing ratio for age cracking is 2.0 or more, The average height of the earrings during drawing may be 2.2 mm or less. In addition, after the 180° banding experiment, surface cracks may not occur in the banded area. Effect of the Invention

[0014] According to the present invention, it is possible to provide an ultrafine-grained 300 series stainless steel having excellent hardness. It is also possible to provide an ultrafine-grained 300 series stainless steel that simultaneously satisfies high strength and high ductility. In addition, through the ultra-fine grain manufacturing technology that realizes banding formability and sound surface properties of the banded portion, it is possible to provide an austenitic stainless steel that is free of surface cracks in the banded portion and has excellent surface roughness. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a diagram showing Σ and Ω values ​​for an example and a comparative example. [Diagram 2] 1 is a photograph showing a microstructure of an example in which the Π value is 6000 or more. [Diagram 3] 1 is a photograph showing an unannealed band in the microstructure of Comparative Example 1 having a π value of less than 6,000. [Figure 4] 1 is a photograph showing that the martensite (red color) fraction (%) is 91.5% and 73.5% when the phase fraction is analyzed by an electron backscatter diffraction (EBSD) at the center of thickness in the transverse direction (TD) plane of the material after cold rolling in the embodiment. [Diagram 5] This is a photograph showing that the martensite (red color) fraction (%) is 48.5% when the phase fraction is analyzed by an electron backscatter diffraction (EBSD) at the center of thickness in the transverse direction (TD) plane of the material after cold rolling in the comparative example. [Figure 6]This is a photograph showing that the percentage (%) of misorientation angles of 15° or more was 96% and 96.5% when the thickness center of the transverse direction (TD) surface of the cold-burned annealed material of the embodiment was analyzed by an electron backscatter diffraction (EBSD) analyzer. [Figure 7] This is a photograph of the center of thickness of the transverse direction (TD) surface of the cold rolled and annealed material of the comparative example, which shows that the percentage (%) of misorientation angles of 15° or more is 92.9% when analyzed with an electron backscatter diffraction (EBSD). Misorientation angles of less than 15° correspond to the red color. [Figure 8] 1 is a photograph showing the average grain size at the center of thickness in a transverse direction (TD) plane of a 0.4 to 2.0 mm steel material manufactured in an example. [Figure 9] 1 is a photograph showing an average grain size at the center of thickness in a transverse direction (TD) plane of a 0.4 to 2.0 mm steel material manufactured in a comparative example. [Figure 10] 1 is a graph showing surface roughness Ra (μm) values ​​according to tensile deformation rates in an example and comparative example 2. FIG. [Figure 11] 1 is a photograph showing the surface roughness Ra (μm) profile according to the tensile deformation rate in an example and a comparative example. [Figure 12] 1 is a photograph showing the height of earrings after drawing in an embodiment and a comparative example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The austenitic stainless steel of the present invention contains, by weight percent, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, 0.02-0.05% N, with the remainder being Fe and unavoidable impurities; The Σ value represented by the following formula (1) may be 180 or more and 240 or less. Formula (1):Σ=105+146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu] In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight percentage of each element, d represents the average crystal grain size (μm), and SPM_El represents the difference in elongation rate (%) before and after Skin Pass Milling.

[0017] Hereinafter, the embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art. The terms used in this application are only used to describe specific examples. For example, singular expressions include plural expressions unless the context clearly requires the singular. In addition, it should be noted that the terms "comprise" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.

[0018] Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be interpreted as having an overly ideal or formal meaning. For example, in this specification, singular expressions include plural expressions unless there is a clear exception in the context. In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values ​​are referred to in order to aid in the understanding of the present invention.

[0019] The austenitic stainless steel of the present invention may contain, by weight, C: 0.04-0.07%, Si: 0.3-0.6%, Mn: 0.5-1.5%, Cu: 0.1-0.4%, Mo: 0.05-0.2%, Ni: 8.0-9.0%, Cr: 18.0-19.0%, N: 0.02-0.05%, and the remainder being Fe and unavoidable impurities.

[0020] The reasons for limiting the alloy composition will be specifically explained below. The C (carbon) content may be 0.04% to 0.07%. C is an element that stabilizes the austenite phase. Taking this into consideration, C can be added in an amount of 0.04% or more. However, if the C content is excessive, a problem may occur in which chromium carbide is formed during low-temperature annealing, thereby reducing intergranular corrosion resistance. Taking this into consideration, the upper limit of the C content may be limited to 0.07%.

[0021] The content of Si (silicone) may be 0.3 to 0.6%. Silicon is an element added as a deoxidizer during steelmaking, and when the steel undergoes the bright annealing process, it forms silicon oxide in the passivation film, improving the corrosion resistance of the steel. With this in mind, silicon may be added in an amount of 0.3% or more. However, if the silicon content is too high, it may cause a problem of reducing the softness of the steel. With this in mind, the upper limit of silicon content may be limited to 0.6%.

[0022] The Mn (manganese) content may be 0.5 to 1.5%. Mn is an element that stabilizes the austenite phase. In consideration of this, Mn may be added in an amount of 0.5% or more. However, if the Mn content is excessive, a problem of reduced corrosion resistance may occur. In consideration of this, the upper limit of the Mn content may be limited to 1.5%.

[0023] The Ni (nickel) content may be 8.0 to 9.0%. Ni is an element that stabilizes the austenite phase and has the effect of softening steel. Taking this into consideration, Ni can be added in an amount of 8.0% or more. However, if the Ni content is excessive, a problem of increased costs may occur. Taking this into consideration, the upper limit of the Ni content can be limited to 9.0%.

[0024] The Cr (chromium) content may be 18.0 to 19.0%. Cr is a major element for improving the corrosion resistance of stainless steel. Taking this into consideration, Cr may be added in an amount of 18.0% or more. However, if the Cr content is too high, the steel material may become hard and the transformation of deformation-induced martensite during cold rolling may be inhibited. Taking this into consideration, the upper limit of the Cr content may be limited to 19.0%.

[0025] The Cu (copper) content may be 0.1 to 0.4%. Cu is an element that stabilizes the austenite phase. Taking this into consideration, Cu may be added in an amount of 0.1% or more. However, if the Cu content is excessive, problems may occur in that the corrosion resistance of the steel material decreases and the cost increases. Taking this into consideration, the upper limit of the Cu content may be limited to 0.4%.

[0026] The N (nitrogen) content may be 0.02 to 0.05%. N is an element that stabilizes the austenite phase and improves the strength of steel. Taking this into consideration, N may be added in an amount of 0.02% or more. However, if the N content is excessive, the steel may become hard and the hot workability may decrease. Taking this into consideration, the upper limit of the N content may be limited to 0.05%.

[0027] The Mo (molybdenum) content may be 0.05 to 0.2%. Mo has the effect of improving corrosion resistance and workability. Taking this into consideration, Mo can be added in an amount of 0.05% or more. However, if the Mo content is excessive, a problem of increased costs may occur. Taking this into consideration, the upper limit of the Mo content may be limited to 0.2%.

[0028] The remaining component is iron (Fe). However, since unintended impurities may be inevitably mixed from raw materials or the surrounding environment during normal manufacturing processes, it is not possible to exclude them. Since the above impurities are known to anyone skilled in normal manufacturing processes, the entire contents of the impurities will not be specifically mentioned in this specification. In addition to controlling the alloy component composition ratio, the austenitic stainless steel of the present invention can be specified as follows. In the present invention, the Σ value represented by the following formula (1) may be 180 or more and 240 or less. Formula (1):Σ=105+146d -1 / 2 +7.36SPM_El+102[C]+154[N]+51.8[Si]+1.4[Mo]-17.7[Cu] Σ is an index representing the hardness of a material, and a larger value indicates a higher hardness. In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight percentage of each element, d represents the average crystal grain size (μm), and SPM_El represents the difference in elongation rate (%) before and after Skin Pass Milling. SPM_El according to one example of the present invention may be 0.01 to 1.2. Skin pass milling can be performed to improve the gloss of the steel material and ensure the shape of the coil.

[0029] In the present invention, the Ω value represented by the following formula (2) may be 2500 or more. Equation (2): Ω = YS * El-500 * ([Ni]+[Cr]+[Cu]+[Mn]) Ω is an index representing high strength and high ductility, and a larger value means a larger product of strength and ductility. In the formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight percentage of each element, YS represents the yield strength (MPa), and El represents the elongation rate (%). The YS and El values ​​refer to values ​​obtained after a tensile test was performed on a JIS13B tensile test piece at room temperature with a crosshead speed in the range of 10 mm / min to 20 mm / min.

[0030] In the present invention, the ASP (Austenitic Stability Parameter) value represented by the following formula (3) may be in the range of −5 to 12. Formula (3): ASP value = 551-462 * ([C]+[N])-9.2 * [Si]-8.1 * [Mn]-13.7 * [Cr]-29 * ([Ni]+[Cu])-18.5 * [Mo] In the formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight percentage of each element. If the ASP value is out of the range of -5 to 12, excessive transformation of the material occurs during the tensile test, and the elongation ratio targeted in the present invention is not satisfied.

[0031] In the present invention, the Π value represented by the following formula (4) may be 6000 or more. Equation (4): Π = 100 * FCRR(Final Cold Rolling Ratio,%)+100 * ASP(Austenitic Stability Parameter)+CAT(Cold Annealing Temperature,℃) Π is an index representing the degree of recrystallization completion, and a larger value means a larger degree of recrystallization. In the above formula (4), FCRR means the reduction rate during cold rolling before final cold roll annealing, ASP means the value of formula (3), and CAT means a value defined by the temperature of the final cold rolled and annealed steel material.

[0032] The average crystal grain size d of the present invention may be 3 to 10 μm. The average grain size means the average grain size at the center of the thickness of the steel material in the TD (Transverse Direction) plane, where t is the total thickness of the steel material. The average means the average value of values ​​measured at any five points, and the center means 1 / 4t to 3 / 4t, where t is the total thickness of the steel material. In the present invention, t may be 0.4 to 2.0 mm. In the case of kitchen and building parts, materials having a thickness of 0.4 to 2.0 mm are often used, and according to the present invention, it is possible to provide a stainless steel having excellent hardness, high strength and high ductility in the corresponding thickness range.

[0033] In the present invention, when the thickness center of the transverse direction (TD) plane is analyzed by an electron backscatter diffraction pattern analyzer (EBSD), the martensite fraction (%) of the cold rolled material may be 60% or more, and the fraction (%) of the misorientation angle of 15° or more after cold rolling and annealing may be 95% or more. When the misorientation angle is 15° or more, it means that recrystallization has occurred after cold rolling and annealing, and when the misorientation angle is less than 15°, recrystallization has not occurred because the difference in orientation angle is small. The average grain size (d), the martensite fraction (%) of the cold rolled material, and the fraction (%) of misorientation angles of 15° or more after cold rolling and annealing were measured by analyzing the orientation at the center of the thickness using an electron backscatter diffraction (EBSD) analyzer with the model name e-Flash FS.

[0034] The pitting potential is a critical potential at which corrosion occurs in the form of holes in a passivated metal material, and the austenitic stainless steel according to the present invention may have a pitting potential of 250 mV or more as a result of measuring the pitting potential at which pitting occurs by applying a potential to the austenitic stainless steel while immersing it in a NaCl solution. Here, the NaCl solution may have a temperature of 30° C. and a concentration of 3.5%. The austenitic stainless steel of the present invention may have a surface roughness (Ra) of 0.50 μm or less when tensile at 30%, a surface roughness (Ra) of 0.36 μm or less when tensile at 20%, and a surface roughness (Ra) of 0.25 μm or less when tensile at 10%.

[0035] In the present invention, when a punch size of Φ50 mm and a disc size of Φ100 mm are used in the drawing process, the limit drawing ratio for age cracking may be 2.0 or more. Also, the average earring height may be 2.2 mm or less. The limit drawing ratio for age cracking is the limit drawing ratio at which age cracking does not occur, and means the ratio of the maximum diameter of the material during drawing to the punching diameter. The average earring height means the average of the sum of all maximum earring heights (H) from the base after drawing minus the sum of all minimum earring heights (h). After the 180° bending experiment according to the present invention, no surface cracks may occur at the bent portion.

[0036] The method for producing the austenitic stainless steel of the present invention will be described in detail below. The method for producing an austenitic stainless steel of the present invention includes the steps of producing a slab containing, by weight, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, 0.02-0.05% N, with the remainder being Fe and unavoidable impurities; hot rolling the slab and hot annealing it to produce a hot rolled steel sheet; The method may include cold rolling the hot-rolled steel sheet and cold-rolling annealing the hot-rolled steel sheet to produce a cold-rolled steel sheet.

[0037] The reason for limiting the range of each alloy element has been described above, and the manufacturing steps will be described in more detail below. The hot rolling annealing can be carried out at a temperature of 1000 to 1150°C. If the hot rolling annealing temperature is less than 1000°C, the residual martensite fraction is high, and the elongation rate may be poor. On the other hand, if the hot rolling annealing temperature exceeds 1150°C, the strength may decrease due to the coarsening of crystal grains. In consideration of this, the hot rolling annealing is performed at 1000 to 1150°C. The cold rolling may have a reduction rate of 60% or more. If the rolling reduction is less than 60%, the amount of TRIP transformation is excessively low, resulting in a low martensite fraction in the cold-rolled material and a high fraction of retained austenite. As the amount of processing-induced martensite decreases, the proportion of reverse-transformed austenite phase by the subsequent low-temperature annealing decreases, and the fraction of retained austenite phase that does not transform into martensite is high, making it difficult to obtain ultrafine crystal grains.

[0038] The cold rolling annealing can be carried out at a temperature of 800 to 950°C. If the temperature of cold rolling annealing is less than 800°C, recrystallization may be insufficient, resulting in a low elongation ratio. On the other hand, if the temperature of cold rolling annealing exceeds 950°C, the particles become coarse and it is difficult to form ultrafine particles of 3 to 10 μm or less, which may cause problems such as surface cracks occurring at the bent portion of the austenitic stainless steel and poor surface roughness. In consideration of this, the cold rolling annealing is performed at 800 to 950°C. The method may be a method for producing an austenitic stainless steel, the method including a step of subjecting the cold rolled steel sheet to skin pass milling. The SPM_El is the difference in elongation rate (%) before and after Skin Pass Milling, and is set to 0.01 to 1.2.

[0039] The present invention will be described in more detail with reference to the following examples. However, the description of the examples is merely for illustrating the implementation of the present invention, and the present invention is not limited by the description of the examples. The scope of the present invention is determined by the matters described in the claims and matters that can be reasonably inferred therefrom.

[0040] <Example> A slab having the composition shown in Table 1 below was hot rolled, then hot rolled and annealed at 1000 to 1150°C, and cold rolled at room temperature to a rolling reduction of 60% or more. Then, cold rolled and annealed at a temperature of 800 to 950°C to produce a cold rolled and annealed material.

[0041] [Table 1]

[0042] Table 2 below shows the values ​​for formulas (1) to (4) based on the component values ​​in Table 1, SPM_El (Skin Pass Mill Elongation, %), FCRR (Final Cold Rolling Ratio, %), CAT (Cold Annealing Temperature, °C) value, and YS (MPa)*El (%) value.

[0043] [Table 2]

[0044] The YS and El values ​​refer to values ​​obtained after a tensile test was performed on a JIS13B tensile test piece at room temperature with a crosshead in the range of 10 mm / min to 20 mm / min.

[0045] The cold rolled and annealed materials were cut into test pieces with a thickness of 0.4 to 2.0 mm. The average grain size (d) at the center of the thickness, pitting potential (mV), presence or absence of surface cracks at the bent part after a 180° bending experiment (the curvature R value of the bent part is the same as the material thickness), and surface roughness at each tensile deformation rate in a uniaxial tensile experiment were measured and are shown in Table 3 below.

[0046] [Table 3]

[0047] The average crystal grain size (d) at the thickness center means the average crystal grain size (d) at the thickness center in the TD (Transverse Direction) plane of a test piece having a thickness of 0.4 to 2.0 mm. The average crystal grain size (d) of the present invention was measured by analyzing the orientation at the center of the thickness using an Electron Back Scatter Diffraction (EBSD) model named e-Flash FS.

[0048] The pitting potential refers to a value measured by immersing a sample in a NaCl solution having a temperature of 30° C. and a concentration of 3.5% and then applying a potential thereto, at which pitting occurs. The tensile deformation rate value means a value obtained by performing a uniaxial tensile test on a JIS 13B tensile test piece at a crosshead speed of 10 to 20 mm / min. The occurrence of bending cracks is determined by a 180° bending experiment in which the curvature R value of the bent part is made the same as the material thickness, and a single bending is performed.

[0049] Table 4 below shows an example of the present invention and shows the average earring height. [Table 4]

[0050] The average earring height is the average of the sum of the maximum height (H) of the earrings from the bottom after drawing minus the sum of the minimum height (h) of the earrings. H is the maximum height, h is the minimum height, and Earring 1 to Earring 4 are the earrings randomly numbered.

[0051] The LDR value and the average Earring height refer to the limit drawing ratio for age cracking and the average Earring height when drawing is performed using a punch size of Φ50 mm and a disc size of Φ100 mm.

[0052] As shown in Tables 1 and 2, in all of Examples 1 to 6, the Σ value of formula (1) satisfies the range of -180 to 240, and the Ω value of formula (2) satisfies the range of 2500 or more, and therefore it is possible to realize excellent hardness, high strength and high ductility. In addition, in all of Examples 1 to 6, the ASP value of formula (3) satisfies the range of −5 to 12, and the Π value of formula (4) satisfies the range of 6000 or more, and therefore no surface cracks occur after the 180° bending experiment.

[0053] As shown in Table 3, in all of Examples 1 to 6, the average crystal grain size (d) value at the center of the thickness of the material in the thickness range of 0.4 to 2.0 mm satisfies the range of 3 to 10 μm, and after uniaxial tensile testing, the surface roughness (Ra) when tensile is 0.50 μm or less at 30%, the surface roughness (Ra) when tensile is 0.36 μm or less at 20%, and the surface roughness (Ra) when tensile is 0.25 μm or less at 10%. In addition, the pitting potential value satisfies the range of 250 mV or more.

[0054] On the other hand, Comparative Examples 2 to 4 do not satisfy the hardness requirement of the present invention since the Σ value is smaller than 180. This can be confirmed from Table 2. Moreover, Comparative Examples 2 to 7 do not simultaneously satisfy the high strength and high ductility requirements of the present invention since the Ω values ​​are less than 2500. This can be confirmed from Table 2. In addition, Comparative Examples 3 to 8 were outside the ASP value limited by the present invention. Comparative Examples 5 to 8, which had an ASP value exceeding 12, showed low elongation due to an excessively fast transformation rate. Comparative Examples 2 to 4, which had an ASP value of less than -5, did not secure ultrafine grains due to a high fraction of retained austenite phase. This can be seen from Tables 2 and 3.

[0055] In addition, Comparative Example 1 has an unannealed band because the Π value is less than 6000, and the steel material including this has bending cracks after the 180° bending experiment. This can be seen from Tables 2, 3 and Figure 3. In contrast, Figure 2 shows that no bands are visible in the microstructure of the Example, and bending cracks do not occur after the 180° bending experiment. Moreover, in Comparative Examples 6 to 8, since the Ni content is low, Mn is added in excess, resulting in low pitting potential values, which causes problems in corrosion resistance. In addition, in Comparative Example 2, the d value is 25.2, which means that the average crystal grain size is coarse and the surface roughness value due to the tensile deformation rate is large compared to the range of the present invention. This can be confirmed from Table 3 and FIG.

[0056] 1 shows the ranges of Σ and Ω values ​​for Examples 1 to 6 and Comparative Examples 1 to 8. Comparative Examples 2 to 8 do not simultaneously satisfy the Σ and Ω values, and are unable to simultaneously satisfy both hardness and high strength-high ductility. Figures 2 and 3 are photographs of the microstructure at the center of the thickness taken by EBSD. The comparative example (Figure 3) shows the presence of unannealed bands in the microstructure. In contrast, the example (Figure 2) shows the absence of unannealed bands in the microstructure. By comparing these, it can be confirmed that the austenitic stainless steel according to the present invention has ultra-fine grains with no band-shaped unannealed portions.

[0057] 4 and 5 show the martensite (red color) fraction (%) when the phase fraction was analyzed by an electron backscatter diffraction pattern analyzer (EBSD) at the center of thickness in the transverse direction (TD) plane of the cold-rolled material of the example and comparative example. The martensite fraction is 60% or more in the example (FIG. 4), and is less than 60% in the comparative example (FIG. 5).

[0058] 6 and 7 show the percentage (%) of misorientation angles of 15° or more when the transverse direction (TD) plane of the material after cold rolling and annealing in the example and comparative example is analyzed by an electron backscatter diffraction (EBSD) pattern analyzer. The percentage (%) of misorientation angles of 15° or more is 95% or more in the example (FIG. 6), which can be compared to less than 95% in the comparative example (FIG. 7). Misorientation angles less than 15° correspond to the red color.

[0059] 8 and 9 are photographs showing the average grain size at the center of thickness in the transverse direction (TD) plane of the manufactured 0.4 to 2.0 mm steel material in the example and comparative example. It can be seen that the average grain size of the comparative example (FIG. 9) is larger than that of the example (FIG. 8). 10 is a diagram showing surface roughness Ra (μm) values ​​after uniaxial tensile tests were performed at a crosshead speed of 10 to 20 mm / min for each deformation rate for Comparative Example 2, in which the average grain size at the surface center of the steel material manufactured in Example was coarser than that of Example 2. It can be seen that when the average grain size exceeds the range of the present invention, the surface roughness Ra value for each deformation rate does not satisfy the range of the present invention.

[0060] FIG. 11 is a photograph showing the surface roughness Ra (μm) values ​​after uniaxial tensile tests were performed for the Examples and Comparative Examples at different deformation rates at a crosshead speed of 10 to 20 mm / min. The x-axis and y-axis are in mm, and the height unit is μm. It can be seen that the Comparative Examples have high surface roughness, as the height increases with increasing deformation. In contrast, it can be seen that the Examples have lower surface roughness than the Comparative Examples, even when deformation is applied. Figure 12 is a photograph showing the earring height after drawing (punch size Φ50mm, disc size Φ100mm). The average earring height refers to the average of the values ​​obtained by adding all the maximum heights (H) of the earrings from the bottom after drawing minus the value obtained by adding all the minimum heights (h) of the earrings. It can be seen that the average earring height of the working example is smaller than that of the comparative example.

[0061] Although the embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by a person having ordinary skill in the art without departing from the concept and scope of the claims set forth below. [Industrial Applicability]

[0062] According to the present invention, it is possible to provide an ultrafine-grained 300 series stainless steel that simultaneously satisfies high strength and high ductility, and also to provide an austenitic stainless steel that is free from surface cracks in bent portions and has excellent surface roughness through a manufacturing technology of ultrafine grains that realize bending formability and sound surface properties of bent portions, and thus the present invention is found to have industrial applicability.

Claims

1. The alloy contains, by weight, 0.04-0.07% C, 0.3-0.6% Si, 0.5-1.5% Mn, 0.1-0.4% Cu, 0.05-0.2% Mo, 8.0-9.0% Ni, 18.0-19.0% Cr, 0.02-0.05% N, with the remainder being Fe and unavoidable impurities; An austenitic stainless steel characterized in that the Σ value represented by the following formula (1) is 180 or more and 240 or less. Equation (1): Σ = 105 + 146d -1/2 + 7.36 SPM_El + 102[C] + 154[N] + 51.8[Si] + 1.4[Mo] - 17.7[Cu] (In the above formula (1), [C], [N], [Si], [Mo], and [Cu] represent the weight percentages of each element, d represents the average crystal grain size (μm), and SPM_El represents the difference in elongation rate (%) before and after Skin Pass Milling.)

2. 2. The austenitic stainless steel according to claim 1, characterized in that the Ω value represented by the following formula (2) is 2500 or more. Formula (2): Ω=YS * E-500 * ([Ni]+[[]+[[#]+[M]) (In the formula (2), [Ni], [Cr], [Cu], and [Mn] represent the weight percentage of each element, YS represents the yield strength (MPa), and El represents the elongation rate (%).)

3. 2. The austenitic stainless steel according to claim 1, characterized in that the ASP (Austenitic Stability Parameter) value represented by the following formula (3) is −5 to 12. Formula (3): ASP value = 551 - 462 * ([C] + [N]) - 9.2 * [Si] - 8.1 * [Mn] - 13.7 * [Cr] - 29 * ([Ni] + [Cu]) - 18.5 * [Mo] (In the formula (3), [C], [N], [Si], [Mn], [Cr], [Ni], [Cu], and [Mo] represent the weight percentages of each element.)

4. 2. The austenitic stainless steel according to claim 1, characterized in that the Π value represented by the following formula (4) is 6000 or more: Equation (4): Π = 100 * Final Cold Rolling Ratio (%) + 100 * Austenitic Stability Parameter + Cold Annealing Temperature (°C) (In the above formula (4), FCRR means the rolling reduction during cold rolling before final cold rolling annealing, ASP means the value of formula (3), and CAT means a value defined by the temperature of the final cold rolled annealed steel material.)

5. 2. The austenitic stainless steel according to claim 1, characterized in that, when the total thickness of the steel material is t, the average crystal grain size (d) value at the center of the thickness of the TD (Transverse Direction) plane is 3 to 10 μm.

6. The austenitic stainless steel according to claim 1, characterized in that the t is 0.4 to 2.0 mm.

7. 2. The austenitic stainless steel according to claim 1, characterized in that the martensite fraction (%) at the center of thickness in the transverse direction (TD) plane after cold rolling is 60% or more.

8. 2. The austenitic stainless steel according to claim 1, characterized in that the percentage (%) of misorientation angles of 15° or more at the center of thickness in a TD (Transverse Direction) plane after cold rolling and annealing is 95% or more.

9. 2. The austenitic stainless steel according to claim 1, characterized in that it has a pitting potential of 250 mV or more in a 3.5% NaCl solution at 30°C.

10. 2. The austenitic stainless steel according to claim 1, characterized in that the surface roughness (Ra) when tensile is 0.50 μm or less at 30%, the surface roughness (Ra) when tensile is 0.36 μm or less at 20%, and the surface roughness (Ra) when tensile is 0.25 μm or less at 10%.

11. 2. The austenitic stainless steel according to claim 1, characterized in that the limit drawing ratio for age cracking of said stainless steel is 2.0 or more.

12. 2. The austenitic stainless steel according to claim 1, characterized in that the average earring height during drawing of the stainless steel is 2.2 mm or less. (The average height of the earrings means the average value obtained by subtracting the value obtained by adding all the maximum heights (H) of the earrings from the bottom after drawing from the value obtained by adding all the minimum heights (h) of the earrings.)

13. 2. The austenitic stainless steel according to claim 1, wherein the stainless steel has no surface cracks at the bent portion after a 180° bending experiment.

Citation Information

Patent Citations

  • Production of cr-ni-based stainless steel thin sheet excellent in surface quality and material quality

    JP1991285023A

  • Austenitic stainless steel sheet excellent in pocket wave resistance and its production

    JP1996260111A

  • Production of austenitic stainless steel thin cast slab

    JP1996300124A

  • Fine grained austenitic stainless steel sheet exhibiting excellent stress corrosion cracking resistance and processability

    JP2011117024A

  • Austenitic stainless steel sheet having excellent detergency, and method for producing the same

    JP2011202253A